Engineering information security : the application of systems engineering concepts to achieve information assurance - Jacobs, Stuart (Hoboken, N.J. : Wiley, 2011)
'Information security is the act of protecting information from unauthorized access, use, disclosure, disruption, modification, or destruction. This book discusses why information security is needed and how security problems can have widespread impacts. It covers the complete security lifecycle of products and services, starting with requirements and policy development and progressing through development, deployment, and operations, and concluding with decommissioning. Professionals in the sciences, engineering, and communications fields will turn to this resource to understand the many legal, technical, competitive, criminal and consumer forces and influences that are rapidly changing our information dependent society.'--Provided by publisher.
'This book discusses why information security is needed and how security problems can have widespread impacts. It covers the complete security lifecycle of products and services, starting with requirements and policy development and progressing through development, deployment, and operations, and concluding with decommissioning. Professionals in the sciences, engineering, and communications fields will turn to this resource to understand the many legal, technical, competitive, criminal and consumer forces and influences that are rapidly changing our information dependent society'--Provided by publisher.
Includes index.
'Book is accompanied by one computer optical disc entitle' Engineering information security : the application of systems engineering concepts to achieve information assurance' bearing the same call number and available at Bahagian Koleksi Media.
Keywords: Computer security; Computer networks -- Security measures; Information technology -- Security measures; Data protection